The Economic Rationale for Industrial Policy in Developing Countries - Škropeková, Andrea; Klosová, Anna, 1942-; Novaes, Jose; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
The role of the government in an industrialization process of developing countries is highly debated. The opinions of scholars diverge. Proponents of extensive government involvement claim that it is a key to sustainable development, while opponents see it as an obstacle to it. The goal of my thesis is to analyze what consequences has had the reduction in the weight of the State in economies of developing countries, especially in Kenya. The thesis is divided into two parts. The first one talks about an evolution of industrial policies in the developing countries. Since the end of colonialism, import substitution had become a dominant pro development strategy in most developing countries, but in 1980s it was substituted by the structural adjustment programmes (SAPs). Those two sets of development strategies are described and assessed in this part. The second part of the thesis is a case study of Kenya. In this part I describe and assess industrialization policies of Kenyan government, analyze a change of its economic freedom since an adoption of SAPs and an influence of an increase in economic freedom on industrialization and social welfare.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; economics of globalisation and european integration [obor dipl. práce]